Implementation of the Tilawati Method with Nagham Bayyati in Improving the Ability to Read the Qur'an at the Babussalam Bosso Class B Al-Qur'an Education Park (TPA), Luwu Regency - Hamsinar Hatta (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to improve the ability to read the Qur'an of students through the application of the Tilawati method with Nagham Bayyati at the Al-Qur'an Education Park (TPA) Babussalam Bosso, class B Luwu Regency. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles, where each cycle consists of planning, implementation, observation, and reflection stages. The subjects of the study were class B students of TPA Babussalam Bosso. The results of the study showed that the application of the Tilawati method with Nagham Bayyati was able to improve the ability to read the Qur'an of students gradually and significantly. In cycle I, the ability to read the Qur'an of students was still in the sufficient category, marked by the presence of errors in the pronunciation of letters, the application of the rules of tajweed, reading fluency, and the lack of mastery of the rhythm of reading and the students' self-confidence. After improvements were made in cycle II, there was a significant improvement, where students began to be able to read more fluently, correctly in pronunciation and tajweed, and were more confident in reading the Qur'an in front of the class. These improvements are not only evident in cognitive aspects, but also in affective aspects, such as increased motivation, interest, and active participation of students in learning. The use of Nagham Bayyati creates a more engaging and enjoyable learning environment, encouraging students to be more active and enthusiastic in their learning. The Tilawati method, implemented gradually, systematically, and repeatedly, also helps students improve and enhance the quality of their reading.